TAX TREATMENT OF COMPANY’S DEBT RELEIF UNDER A REORGANIZATION PLAN ACCORDING TO THE LEGAL FRAMEWORK OF NORTH MACEDONIA - Goran Koevski, Darko Spasevski (My University, 2020)
Company restructuring (reorganization) process during bankruptcy involves wide range of legal issues. The reason for this is the complexity of the process itself. In general, the process is governed by the Law on Bankruptcy. However, some of the challenging legal issues can be related to the tax regulation. In this respect, one of the most important issue is the tax treatment of debt waivers (debt relief) under accepted reorganization plan. The central dilemma here is whether this debt relief is taxable income, or this amount can be qualified for tax exemption? This issue can be examined from two perspectives. First, from the position of the bankruptcy creditor whose claim is canceled under the reorganization plan. Second, from the standpoint of the bankruptcy debtor, whose business undertaking is under reorganization. The authors of this paper are analyzing the de lege lata legal framework of North Macedonia regarding this issue and providing for some de lege ferenda perspectives by using comparative law methodological approach.
Keywords: reorganization plan, tax treatment, debt relief